2019
DOI: 10.1111/jan.13962
|View full text |Cite
|
Sign up to set email alerts
|

Implementing primary healthcare nurse practitioners in long‐term care teams: A qualitative descriptive study

Abstract: Aim To identify the conditions needed to implement nurse practitioners (NP) in long‐term care (LTC) in Québec, Canada. Design A qualitative descriptive study was undertaken. Methods Semi‐structured interviews (N = 91) and socio‐demographic questionnaires were completed with providers and managers from May 2016–March 2017. Nurse practitioner activity logs were compiled at three sites. Content analysis was used. Results All sites initially implemented a shared care model but not all sites successfully implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 31 publications
(45 reference statements)
5
26
0
Order By: Relevance
“…This paper reports on the findings from field notes and a prospective cohort study of residents receiving NP care. Findings from the qualitative descriptive study describing the views of providers and managers are reported elsewhere [54].…”
Section: Aimsmentioning
confidence: 99%
“…This paper reports on the findings from field notes and a prospective cohort study of residents receiving NP care. Findings from the qualitative descriptive study describing the views of providers and managers are reported elsewhere [54].…”
Section: Aimsmentioning
confidence: 99%
“…A cost savings analysis was completed using a prospective observational study as part of a quality improvement project in six long-term care facilities in Qu ebec, Canada (Kilpatrick et al, 2020).…”
Section: Designmentioning
confidence: 99%
“…Each site sent anonymized extractions each week to the research coordinator who reviewed the submissions to ensure that no data were missing. Each site coordinator was contacted to clarify any questions (Kilpatrick et al, 2020).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified that provider judgements or beliefs about team functioning and effectiveness are influenced by processes that include decision-making, communication, cohesion, care coordination, problem-solving, a focus on the needs of patients and families, as well as role clarity and trust among team members 16,17. The measurement of these team processes has been a critical challenge because of the financial and human resources required and the lack of validated instruments.…”
Section: Introductionmentioning
confidence: 99%